Triazole rizatriptan Induces Liver Toxicity through Lysosomal/Mitochondrial Dysfunction - Fard, J. K.; Hamzeiy, H.; Sattari, M.; Eftekhari, A.; Ahmadian, E.; Eghbal, M. A. (Drug Research, 2016)
Background: Triptans are used as antimigraine agents. Some cases of hepatotoxicity by triptans have been reported. However, the exact mechanism of triptan-induced hepatotoxicity is not clear yet.Methods: In this study, the cytotoxic effects of rizatriptan were investigated in freshly isolated rat hepatocytes using accelerated cytotoxicity mechanism screening. We designed experiments to evaluate toxicity markers, such as cell death, reactive oxygen species (ROS) formation, lipid peroxidation, mitochondrial membrane potential, lysosomal membrane integrity and the amount of reduced and oxidized glutathione in the rizatriptan-treated hepatocytes.Results: Cytotoxicity caused by rizatriptan in rat hepatocytes was concentration-dependent. An increase in ROS formation accompanied by a significant rise in lipid peroxidation, mitochondrial depolarization and loss of lysosomal membrane integrity was observed. Cellular glutathione reservoirs were decreased and a significant amount of oxidized glutathione was formed. All the aforementioned rizatriptan-induced cellular events were significantly (p<0.05) prevented by ROS scavengers, antioxidants, endocytosis inhibitors and adenosine triphosphate (ATP) generators. Also, the present results demonstrated that CYP450 is involved in rizatriptan-induced oxidative stress and cytotoxicity mechanism and different CYP450 inducers had different effects on the toxicity.Conclusion: It is suggested that the adverse effect of rizatriptan towards hepatocytes is mediated by oxidative stress and the hepatocytes lysosomes and mitochondria play an important role in rizatriptan-induced cell injury.
Keywords: oxidative stress; reactivity oxygen species; hepatotoxicity; rizatriptan; lysosome; mitochondria